Students’ Character Development and Lecturer’s Teaching Profile in Introduction to Elementary Mathematics Class Using Logical Mathematics Materials That Based on Character Education - Nurjanah Nurjanah; Usep Kosasih; Dinny Mardiana (Proceedings of AICS - Social Sciences, 2016)
This study is following up previous one about the development of Introduction to Elementary Mathematics course materials using character education approach; which had resulted in a material about mathematical logic using character education approach which is valid, practical, and effective. The subjects are freshmen of the Department of Mathematics Education, Faculty of Teacher Training and Educational Sciences, Nusantara Islamic University, Bandung, Indonesia. This study employed qualitative action research design with practical action research type. The action research was carried out in five classroom sessions where every session was divided into four practical action research steps as follows: identifying focus area, collecting the data, analyzing and interpreting data, and developing an action plan. All classroom sessions are carried out by referring to the main materials that were previously developed; and they all implemented contextual approach based on character education stages: moral knowing, moral feeling, and moral actions. This study used the following instruments to gather the data: observation over students and instructors’ activities, questionnaires, and interview guidelines. This study has successfully found that both students’ character development and instructor’s teaching profiles dynamically improve when the instruction session implement materials that integrated character components into mathematical logic materials.